Comparing Teacher and Learner Perceptions of Emergency Remote Teaching (ERT) - Sharon Hartle; Giorgia Andreolli (Iperstoria, 2023)
As a result of the shift to Emergency Remote Teaching (ERT), changes occurring both inside and outside virtual classrooms have led to discussions of the possibly detrimental effects of digital pedagogies on learning (Hodges et al. 2020). The challenges faced by the educational community during this time have been addressed on multiple occasions (Ferri, Grifoni and Guzzo 2020, Ferritti 2020, Maldonado and De Witte 2021), yet debate also exists around the “transformative” potential of ERT (Reimers et al. 2020). The move to this format has, in fact, created new teaching and learning spaces, and the many lessons to be learned from this situation will reveal themselves in time to come, as the result of careful investigation. To this end, our paper reports the findings of a small-scale study carried out at the University of Verona in 2020. A qualitative approach was adopted in the analysis of interview data, conducted with those directly involved in ERT. The objective was to explore the perceptions of both language students and teachers concerning their experiences with learning and teaching technologies. The paper examines which emerging themes may be worth integrating into university language teaching approaches going forward.